16 Evaluation of a citywide program to reduce aggressive driving between commercial and passenger vehicle drivers. (9th June 2015) - Cook, Larry; Telford, Russell; Olson, Lenora
Abstract : Introduction: The inquisitive nature of children and their interaction with the environment makes them prone to injuries. In school children are involved in many activities like play, sports, academics all of which can predispose them to injury if there is lack of supervision and preventive measures are not taken. The objective was to review types of injuries that occur within school environment of Karachi. Methods: This ongoing study since August 2013 is being conducted in Karachi, Pakistan. The data is collected from class teachers on injuries among children that took place in last academic year. These class teachers represent both public and private schools in Karachi. Only those injuries are being included that caused loss of at least one-half day of school and/or required medical attention and treatment from a healthcare provider in school or healthcare facility. So far 62 class teachers from 25 schools have completed injury record form. A total of 80 injuries have been reported. Results: Out of 80 injuries reported, about 67.5% (n = 54) occurred in boys giving a male female ratio of 2.08:1. The frequently effected age group was between 8 – 11 years of age (n = 30, 37.5%). Majority of these injuries occurred inside the school (n = 78, 97.5%) and more than half occurred during sports activities (n = 44, 55%). Face (n = 22, 27.5%), head (n = 18, 22.5%) and hand (n = 17, 21.3%) were the most commonly injured body parts. The most common mechanism was fall (n = 32, 40%). Most common treatment given was bandage (n = 17, 21.25%), stiches (n = 12, 15%) and plasters (n = 9, 11.25%). Almost all the students were under supervision (n = 78, 97.5%) at the time of injury by a teacher (n = 52, 65%). Conclusion: Children are prone to get injuries within school environment, therefore there is need for developing injury prevention and management plans tailored to schools in resource constraint settings.